Professional Rights of the teachers in private Schools in Nepal - Chatkuli, Shyam Bahadur (International Research Journal of MMC, 2020)
The teachers of self-financed schools in Nepal have professional rights or not’ is the subject of the study. All the rules, regulations, and acts including the constitution should be professional or occupational friendly for a developing country. The teaching profession in private schools like Nepal is a very significant job because of producing manpower without devouring government budget. The teachers must have the rights to enjoying professional rights. Recently private schools teachers are in the condition of dissatisfaction of their job and demanding to implement social security fund. Until and unless working people can’t enjoy the professional rights, a country cannot be the democratic socialist country because of exploitation. It remains as a feudal society as it was in the ancient times where owners remain as masters and teachers remain as slaves. To produce self-respect citizens from private schools, all the teachers of self-financed schools must enjoy professional right because they work with brains, not with registers and machines. The investigation of this study is the teachers and their professional rights in all types of private and institutional self-financed schools in Nepal. Both the qualitative and quantitative i.e. mixed method has been applied. This study has explored that teachers from private schools are prohibited from enjoying professional rights.